2020
DOI: 10.1097/pr9.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences in parents of youth with chronic pain: prevalence and comparison with a community-based sample

Abstract: Supplemental Digital Content is Available in the Text. Parents of youth with chronic pain reported high rates of adverse childhood experiences, including significantly higher rates of physical neglect than a community-based sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Procedures for the broader PATH study have been reported elsewhere. 2 , 32 , 33 , 34 , 35 , 41 , 48 Eligibility for initial enrollment in the PATH study included youth between 10-18 years of age who had been identified by a health care provider as having chronic pain (i.e., pain ≥ 3 months 30 ) without an underlying disease (e.g., cancer). Exclusion criteria for both youth and parents included being unable to read/speak English, a diagnosis of a neurodevelopmental disorder (e.g., intellectual disability, autism spectrum disorder), and/ or a serious mental health disorder (e.g., schizophrenia, psychotic disorder).…”
Section: Methodsmentioning
confidence: 99%
“…Procedures for the broader PATH study have been reported elsewhere. 2 , 32 , 33 , 34 , 35 , 41 , 48 Eligibility for initial enrollment in the PATH study included youth between 10-18 years of age who had been identified by a health care provider as having chronic pain (i.e., pain ≥ 3 months 30 ) without an underlying disease (e.g., cancer). Exclusion criteria for both youth and parents included being unable to read/speak English, a diagnosis of a neurodevelopmental disorder (e.g., intellectual disability, autism spectrum disorder), and/ or a serious mental health disorder (e.g., schizophrenia, psychotic disorder).…”
Section: Methodsmentioning
confidence: 99%
“…Families were recruited as part of the Pain and Mental Health in Youth (PATH) study, a broader program of research examining a myriad of cognitive, behavioral, neurobiological, and social factors in the co-occurrence of chronic pain and internalizing mental health disorders in youth. To date, studies have used data from the PATH study to examine diagnostic uncertainty, sleep disturbances, daily relations between parent and child functioning, intolerance of uncertainty, attentional biases, and adverse childhood experiences [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. As such, the aims of the current study are distinct from these published studies.…”
Section: Methodsmentioning
confidence: 99%
“…Most notably, it has been established that offspring of parents with chronic pain have an increased risk of developing chronic pain and the associated negative psychological outcomes (e.g., PTSD symptomology) [ 2 , 18 ]. Evidence also suggests that parental ACEs confer risk of poor health outcomes in children [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Given that parental trauma symptomology has been shown to play a role in pediatric chronic pain [ 17 , 18 , 19 , 23 , 27 , 28 , 29 , 30 ], it may be that parent ACEs also impact chronic pain in children.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also suggests that parental ACEs confer risk of poor health outcomes in children [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Given that parental trauma symptomology has been shown to play a role in pediatric chronic pain [ 17 , 18 , 19 , 23 , 27 , 28 , 29 , 30 ], it may be that parent ACEs also impact chronic pain in children. Recent evidence suggests that rates of ACEs, particularly maltreatment (physical neglect), are high among parents of youth with chronic pain, which may suggest they confer risk for the onset of child pain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation